The Influence of Price, Design, and Location on Consumers’ Purchase Decisions of Residential Housing Products : Study at Dwija Regency, Ir. H. Juanda Street, Ponorogo - Ani; Wijianto; Sri Hartono (Malaqbi Publisher, 2026)
Marketing management is the science of selecting target maerkets and achieving, and retaining them by creating and delivering superior customer value, thereby crating satisfaction. The purpoe of this study is to determine the effect of price, design, and location on consumer purchasing decisions for housing products in Dwija Regency Jalan Ir. H. Juanda Ponorogo. The sample is a consumer in the Dwija Regency Ponorogo housing estate who has purchased or who has occupied housing using the saturated sample technique and a sample of 55 respondents. The analysis used in this study uses multiple linier regression analysis using the SPSS 22 progam. This study resulted in a partial test (t) for odel 1 as follows: price (X1) = 0.020, design (X2) = 0.014 and location (X3) = 0.024.